Intraocular Pharmacokinetics and Safety of Subretinal Injection Compared with Intravitreal Application of Conbercept in Vitrectomized Rabbit Eyes - Teng-teng Yao; Xiao-liang Jin; Yuan Yang; Yi-xiao Wang; Ya-li Zhou; Fang-lin He; Zhao-yang Wang (Journal of Ophthalmology)
Purpose. To evaluate the ocular pharmacokinetic properties of subretinal conbercept injection in vitrectomized rabbit eyes and to compare them with those by intravitreal injection. Methods. The following groups of New Zealand white rabbits received conbercept injections (0.5 mg/0.05 ml): a subretinal group (subretinal injection in vitrectomized eyes), an intravitreal group (intravitreal injection in vitrectomized eyes), and a control group (intravitreal injection in nonvitrectomized eyes). Drug concentrations in the aqueous humor (AH), the vitreous humor (VH), and the retina were measured by the enzyme-linked immunosorbent assay (ELISA), and pharmacokinetic parameters were calculated. Ophthalmic B-ultrasonography, electroretinogram (ERG), and hematoxylin and eosin (H&E) staining were performed to evaluate the safety of subretinal injection. Results. On the 28th day after injection, the drug level in the subretinal group was significantly higher than that in the intravitreal group in the AH (0.90 ± 0.25 μg/ml and 0.11 ± 0.07 μg/ml, P<0.001, respectively) and the VH (5.00 ± 3.86 μg/ml and 0.40 ± 0.34 μg/ml, P=0.016, respectively). The clearance rate from AH and VH exhibited terminal half-life times of 9.88 ± 6.48 days and 6.14 ± 1.69 days by the subretinal application, which were significantly longer than the half-life in AH (3.34 ± 0.58 days, P=0.004) and VH (3.12 ± 0.45 days, P=0.002) by the intravitreal application to the vitrectomized eyes. No significant physiological and anatomical functional changes in the retina were observed after subretinal conbercept injection. Conclusions. Our study indicates that applying conbercept by subretinal injection can reduce the drug clearance rate and sustain a long maintenance period in ocular tissue, which suggests that subretinal conbercept injection may be a potentially valuable treatment option.